Recurrent Gliosarcoma in Pregnancy - İsmail Gülşen; Hakan Ak; Tevfik Yilmaz; Mehmet Deniz Bulut; İsmet Alkış; İrfan Bayram (Case Reports in Neurological Medicine)
Gliosarcoma is a rare tumor of the central nervous system and it constitutes about 1 to 8% of all malignant gliomas. In this report we are presenting a recurrent gliosarcoma case during a pregnancy in a 30-year-old woman. This is the first report presenting gliosarcoma in the pregnancy.